2009
DOI: 10.1016/j.bbrc.2009.01.150
|View full text |Cite
|
Sign up to set email alerts
|

The hepatic circadian clock is preserved in a lipid-induced mouse model of non-alcoholic steatohepatitis

Abstract: Recent studies have correlated metabolic diseases, such as metabolic syndrome and non-alcoholic fatty liver disease, with the circadian clock. However, whether such metabolic changes per se affect the circadian clock remains controversial. To address this, we investigated the daily mRNA expression profiles of clock genes in the liver of a dietary mouse model of non-alcoholic steatohepatitis (NASH) using a custom-made, high-precision DNA chip. C57BL/6J mice fed an atherogenic diet for five weeks developed hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Previously, we reported that the amount of ethanol-dependent triglyceride accumulation is dependent on the fat content of the diet suggesting an interaction between ethanol and fat [31]. However, daily oscillations of clock genes were shown to be maintained in the liver of mice fed a high-fat atherogenic diet (34.3% fat) for 5 wk, despite the presence of non-alcoholic steatohepatitis [32]. Studies using ethanol in drinking water typically show little to no hepatic steatosis with lower blood alcohol levels in the dark phase presumably due to metabolic tolerance [33], whereas in the current study blood alcohol levels in the dark phase (ZT15) were >300 mg/dL.…”
Section: Discussionmentioning
confidence: 92%
“…Previously, we reported that the amount of ethanol-dependent triglyceride accumulation is dependent on the fat content of the diet suggesting an interaction between ethanol and fat [31]. However, daily oscillations of clock genes were shown to be maintained in the liver of mice fed a high-fat atherogenic diet (34.3% fat) for 5 wk, despite the presence of non-alcoholic steatohepatitis [32]. Studies using ethanol in drinking water typically show little to no hepatic steatosis with lower blood alcohol levels in the dark phase presumably due to metabolic tolerance [33], whereas in the current study blood alcohol levels in the dark phase (ZT15) were >300 mg/dL.…”
Section: Discussionmentioning
confidence: 92%
“…It is therefore conceivable that clock genes play a role in lipid metabolism in the liver and that circadian dysregulation or impairment of the clock mechanism can contribute to the development of NAFLD. For example, in another study by Ando and colleagues, no changes were detected in the rhythmicity of hepatic clock gene expression and rhythmically expressed genes in a mouse model of non-alcoholic steatohepatitis [31]. In this model, mice were fed an atherogenic diet that induced steatosis, inflammation, cellular ballooning, stellate cell activation, hepatic insulin resistance, lipid peroxidation and oxidative stress in the liver.…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 96%
“…Despite the presence of these extensive pathological changes, the hepatic circadian clock was unimpaired. These findings provide evidence that the circadian clock is protected against alterations in the intracellular environment and that impairment of the circadian clock may present a cause, rather than a consequence, of metabolic disease [31].…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 97%
“…In contrast to MCD-induced steatohepatitis, animals receiving an atherogenic diet also exhibit systemic insulin resistance, which can be exacer-bated by increasing the fat content [41] . In these models, the expression of genes for fatty acid synthesis, such as SREBP-1c and fatty acid synthase, are upregulated, while the expression levels of genes involved in mitochondrial fatty acid ␤ -oxidation are repressed, resulting in dysregulation of mitochondrial energy production, carbohydrate metabolism and lipid metabolism in hepatocytes [41,42] .…”
Section: Animal Models -Turning Years Into Weeksmentioning
confidence: 99%